Academic self-concept, teacher’s supports and student’s engagement in the school - Nur Saqinah Galugu; Samsinar Samsinar (Program Studi bimbingan Konseling PPs UNM Makassar, 2019)
Students' engagement in school is a condition where the students can engage in learning activity well, it seems by the students' ability and willingness to engage in the school activity. This research aims to examine the role of academic self-concept as the moderate variable on the relationship between teacher's support and students' engagement in school. This research uses qualitative through the correlational method. Students' engagement is measured by the student's engagement at school questionnaires (SESQ). While the teacher's support is measured by the perceived teacher academic support scale (PTASS). Academic self-concept is a moderate variable that is measured by using the academic self-concept scale (ASC) by measure on two aspects namely students' confidence and students' effort in the academic aspect. Testing hypotheses have one by using moderated regression analysis (MRA). The results show that the relationship between the teacher's support and students' engagement in school is increasingly strengthened by the presence of academic self-concept as a moderated variable. Teacher's supports such as emotional supports in the learning process can enhance academic self-concept positively. The positive self-concept among the students encourage to develop student's self-regulation and achievement academic and automatically increase student's engagement in the learning process.